2017
DOI: 10.1103/physrevphyseducres.13.010114
|View full text |Cite
|
Sign up to set email alerts
|

Peer discussions in lecture-based tutorials in introductory physics

Abstract: This study analyzes the types of peer discussion that occur during lecture-based tutorial sessions. It focuses in particular on whether discussions of this kind have certain characteristics that might indicate success in the post-testing phase. The data were collected during an introductory physics course. The main data set was gathered with the aid of audio recordings. Data-driven content analysis was applied in the analysis to facilitate the placement of students' discussions in particular categories related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…With group activities and other learning exercises this has shown to be the best method in how the tutorials were carried out. For example, this is consistent with the work of Leinonen [9] that found that giving students the chance to discuss amongst themselves and teach each other is more effective than learning from a professor.…”
Section: Teaching Methodssupporting
confidence: 86%
“…With group activities and other learning exercises this has shown to be the best method in how the tutorials were carried out. For example, this is consistent with the work of Leinonen [9] that found that giving students the chance to discuss amongst themselves and teach each other is more effective than learning from a professor.…”
Section: Teaching Methodssupporting
confidence: 86%
“…Heller and Hollabaugh (1992) investigated students groups solving context-rich physics problems and identified that group size, heterogeneity and member's personality as important features that would affect group performance. Consequently, group-size does matter, being groups of three and four the ones that generated the better outcomes, which was supported by supported by Leinonen, Asikainen, and Hirvonen (2017). In terms of group composition, heterogeneous groups tend to perform better, with medium and low ability students complying an important role in regulating groups' processes, and suggesting simple but effective ideas.…”
Section: Group Effectivenessmentioning
confidence: 75%
“…The group condition. A study done by (Leinonen et al, 2017) revealed that in a larger group, there was a potential weakness of student participation in the smooth discussion. The recommended number of students in each group is 3 to 4 students.…”
Section: Resultsmentioning
confidence: 99%